Characteristics and Development Prospects of Lithuanian Gymnasium Students’ Linguistic Behaviuor - Tamulionienė, Aurelija (Verbum, 2025)
The article, based on data from a comprehensive study conducted during the 2023-2024 academic year on the linguistic behaviour of gymnasium students’ in everyday life, discusses the results of language choice in various daily situations from the perspectives of language vitality and communicative adaptation theories. These results reflect current realities and indicate expected changes. The study revealed that young people's linguistic environment is predominantly Lithuanian (the language used at home, in communication with friends, in public spaces, when reading books, and when expressing feelings and emotions). The influence of English is more pronounced in the online sphere and in communication on social media. The interaction between the standard language and dialects shows limited use of dialects in everyday communication, however, it is noteworthy that dialect use remains a significant symbol of connection with one’s native place, language, and tradition. The use of other languages may be determined by internal and external factors - either as a conscious choice to speak another language or as a necessity dictated by circumstances. The results of this study outline two directions of linguistic behaviour: the first indicates a strong and close identity connection with the Lithuanian language, while the second reveals young people’s openness to other languages and cultures.
Keywords: Lithuanian language; gymnasium students’ language; language vitality; linguistic behaviuor; communication adaptation